The impact of internet finance on green technology innovation in manufacturing companies --mediating role based on financing constraints - Yu, Yaguai; Li, Yuting; Ni, Taohan; Gao, Chuming (Frontiers in Environmental Science, 2023)
To empirically analyze the relationship between internet finance and green technology innovation of manufacturing firms, this paper selects listed manufacturing firms from 2011 to 2020 as the sample. A panel regression model is then constructed and a causal stepwise regression test is used to examine the mediating effect of financing constraints on the role of internet finance in green technology innovation. The results show that the growth of Internet finance can significantly alleviate the financing problems of industrial enterprises and promote their adoption of green technologies. Further research found that enterprises in less developed areas in central and western China, in regions with weaker environmental regulations and smaller size, play a greater role in promoting green technology innovation. Consequently, improving the incentive system for Internet finance to promote green technology innovation in enterprises can effectively link the development of Internet finance and green innovation in enterprises, promote the development of ecological civilization, and serve as an important decision-making tool to help China achieve its “double carbon” goal.